Use of ceramic tools for machining nickel based alloys - Richards, N.; Aspinwall, D. (International journal of machine tools & manufacture, 1989)
The paper is the first of two dealing with the use of ceramic tool materials for the machining of nickel based alloys. While the second contribution presents the results of detailed machinability tests, involving a cross-section of current nitride, superhard and whisker reinforced ceramic tooling products, this first paper comprehensively reviews existing literature on the subject. Following an assessment of tool wear characteristics, such as depth-of-cut notching and the underlying mechanisms involved, in particular the effects of applied mechanical stress and high interface temperatures, details are given of the composition, structure, physical properties and cutting performance of various state-of-the-art ceramic tool materials. Although only recently available commercially, whisker reinforced composite tools, comprising an alumina matrix with approximately 25% by volume silicon carbide whiskers, are reported to be capable of operating at cutting speeds up to 750 m/min on some nickel based alloys.